STUDI MORFOLOGI SERBUK SARI PADA BEBERAPA VARIETAS Coleus scutellarioides L. - M, Des; Chatri, Moralita; Mikaf, Ficil (IAIN Batusangkar, 2013)
Coleus scutellarioides is Labiatae. It have much varieties based on the leave shapes and colors. In the identification is not enough based on morpho-logical organ characters, but it can also based on the pollen morphology. The purpose of this study to determine the pollen morphology of seven varieties of Coleus scutellarioides. The research was conducted in the laboratory of Botany Department of Biology, State University of Padang, in April-May 2012. Seven varieties of Coleus used came from Padang Panjang and Lintau Buo. Pollen taken from bloomed flowers and it made be slides used acetolisis methods and 1% safranin staining method. Data were analyzed descriptively included pollen unit, polarity, symmetrically, size, shape, aperture, and the shape of pollen surface. The seven Coleus pollen varieties have similirity of the type of monad pollen unit, polarity isopolar type, radial symmetry, type colpate with 6 aperture located in the equatorial (Stephano), and reticulate surface-shaped pollen. Prolate spheroid shapes found in var. Eleanor, subprolate forms in var. Batique Fetish, var. Fack, var. Apricot, var. Burgundy Giant, var. Eleanor, and var. Flambe. Whereas prolate shapes found in var. Batique Fetish, var. Fack, and var. Va Va Boom. Pollen morphology of seven varieties of Coleus scutellarioides have different shape and the author have found 3 shape of pollen as the prolate spheroidal, subprolate and prolate.Key words: pollen, Coleus scutellarioides, identification